Possible roles of insulin signaling in osteoblasts. (November 2014) - Pramojanee, Sakarat N.; Phimphilai, Mattabhorn; Chattipakorn, Nipon; Chattipakorn, Siriporn C.
Abstract Insulin and its downstream signaling pathway are indispensable for postnatal bone growth and turnover by having influence on both osteoblast and osteoclast development. Insulin signaling regulates both bone formation by osteoblasts and bone resorption by osteoclasts; however, the regulation occurs mainly through the insulin signaling pathway within osteoblasts. An impairment of osteoblastic insulin signaling leads to an impaired bone quality by affecting osteoblast proliferation, differentiation and survival. The insulin signaling pathway and MAPK and PI3K/Akt pathways play pivotal roles in the differentiation, function and survival of bone cells. Current evidence suggests that osteoblastic insulin signaling not only modulates bone growth and turnover but is also required for energy metabolism. Several mice models with impaired insulin signaling exhibited both bone and metabolic phenotypes, including symptoms of low bone mass, obesity, glucose intolerance and insulin resistance. In this review, we discuss the key findings that suggest a pivotal role of osteoblastic insulin signaling in both bone and energy metabolism.